Design and Development of Low Cost Two Axis Filament Winding Machine - Mateen, M. A.; Ravi Shankar, D.V.; Manzoor Hussain, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Composite materials are been used in many applications these days, as they have demonstrated there competence and sustainability to considerable distance. Among the various manufacturing techniques filament winding method is the cheap and easy way of fabrication symmetric components. The present work focuses on design and development of a low cost two axis laboratory size filament winding machine (FWM) capable of developing pipes of 50 mm minimum internal diameter and a maximum length of 1000mm. The speed control units developed in the present study facilitates in independently controlling the speeds and direction of the mandrel and the end-effecter in an attempt to achieve the winding angle ranging from 10º to 90º. The speed of the mandrel and the end – effecter could be varied from 0 – 480 rpm and 0 – 500 rpm respectively. A 16-bit RISC single-chip microcontroller is used to logically process the required control signals to achieve the required the motion in the machine. Tubular samples of 50 mm internal diameter and 53mm external diameter were prepared from the developed FW machine and where with a good product quality.